ICCREM 2019. proceedings of the International Conference on Construction and Real Estate Management 2019, May 21-24, 2019, Banff, Alberta, Canada - Wang, Yaowu; Al-Hussein, Mohamed; Shen, Qiping (American Society of Civil Engineers, 2019)
This collection contains 110 peer-reviewed papers on innovative construction project management and construction industrialization. Topics include: intelligent construction and construction informatization; innovative construction project management; construction industrialization and sustainability; and real estate and land management. These papers will be of interest to researchers, engineering practitioners, developers, and planners from universities, consulting firms, and financial institutions.